Lifestyle interventions for people with a severe mental illness living in supported housing: A systematic review and meta-analysis - Koomen, Lisanne E. M.; van der Horst, Marte Z.; Deenik, Jeroen; Cahn, Wiepke (Frontiers in Psychiatry, 2022)
Although supported housing facilities (SHF) appear to be an ideal setting for supporting people with severe mental illness (SMI) to obtain a healthier lifestyle, little is known about the effects of lifestyle interventions in SHF and the factors contributing to successful implementation. We performed a systematic review and meta-analysis to assess the effect of lifestyle interventions on mental and physical health in people with SMI in SHF, and reviewed which intervention factors contribute to successful implementation. A meta-analysis using a random effects model was undertaken. Discussions were reviewed to identify factors that foster successful implementation. Of 7401 identified studies, 9 RCTs (n=1260) were included for the systematic review and 8 (n=1187) for the meta-analysis. Improvements in weight (n=3), BMI (n=1), 6-Minute Walk Test (n=1) and metabolic criteria (n=2) were seen. In the meta-analysis we only found a small effect for a decrease in waist circumference. Reviewing factors involved with the implementation showed that the most successfully implemented interventions were multidisciplinary and integrated into standard care. In conclusion, we found limited evidence for the effectiveness of lifestyle interventions on physical health for those living in SHF. To reliably examine the effects on mental and physical health more studies with high involvement of staff and participants are needed.